2010
DOI: 10.3109/15622975.2010.491127
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic neurotransmission in early Parkinson's disease: A pilot study to assess implications for depression in this disorder

Abstract: Our results support the hypothesis that serotonergic neurotransmission is decreased in untreated PD and suggest that a low serotonergic activity may be related to the dopamine pathology in PD. This could be related to the high prevalence of depression in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 47 publications
1
29
0
2
Order By: Relevance
“…Juckel et al (2008a) reported that patients with various stages of schizophrenia had weaker LDAEP compared with normal controls. Beucke et al (2010) also found a significant difference of LDAEP between controls and patients of early Parkinson. The authors concluded that their finding supports the dysfunction of serotonergic system in schizophrenia and Parkinson.…”
Section: Discussionmentioning
confidence: 69%
“…Juckel et al (2008a) reported that patients with various stages of schizophrenia had weaker LDAEP compared with normal controls. Beucke et al (2010) also found a significant difference of LDAEP between controls and patients of early Parkinson. The authors concluded that their finding supports the dysfunction of serotonergic system in schizophrenia and Parkinson.…”
Section: Discussionmentioning
confidence: 69%
“…Depression and apathy in PD may be associated to different factors: depression is probably related to the dysfunction of different neurotransmitters, including dopamine, serotonin and norepinephrine [65][66][67][68][69][70][71], to the effects of dopaminergic therapies on other neurotransmitters [72] and to the amygdalar dysfunction [73][74][75] that affects patients since the early stages of PD and is considered an hallmark of depression [76]. Apathy is probably more related to the hypostimulation of OFC, an area involved in affective processing, which is affected in PD patients in moderate/advanced stages of the disease [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…HA and PD could be caused by shared genetic and/or early environmental risk factors that predispose subjects, independently, to both PD and certain personality traits: therefore the presence of affective disorders in PD may be characterized as a part of a chronic maladaptive strategy belonging to an affective/ personality trait, rather than being state dependent [86][87][88][89]. Conversely, the increased HA could be state dependent and due to the presence of affective disorders; in this perspective many factors could contribute to the high tendency toward negative affect of PD patients, resulting in high rates of affective disorders and high HA: the deficit of serotonin [90][91][92] that characterizes this clinical population since the early clinical stages [93]; the early amygdala dysfunction of PD [94][95][96] which is considered a hallmark of depression and anxiety [97,98]; the executive dysfunction that characterizes PD patients from the early clinical stages [99] and that represents a risk factor for the development of depression in the elderly [100].…”
Section: High Harm Avoidancementioning
confidence: 90%